answersLogoWhite

0


Best Answer

2a + 10 + 5a - 2 =

(2a + 5a) + (10 - 2) =

7a + 8

User Avatar

Wiki User

โˆ™ 2015-10-04 04:57:22
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

๐Ÿ““
Create a Study Guide

Add your answer:

Earn +20 pts
Q: How do you simplify 2a plus 10 plus 5a-2?
Write your answer...
Submit
Related questions

4a plus 5a2 - 2a x 3a?

depends what the value of 'a' is.


What is 2a to the power of 2 plus 3a to the power of 2?

2a2+3a2 = 5a2


Simplify fully 4a plus 5b minus 2a plus b?

2a+6b


Simplify 3aยฒ plus a-aยฒ plus 5a?

2a² + 6a


Simplify the answer of 4a plus b-2a-2b?

It is 2a-b simplified


How do you simplify 2a plus 5a?

Add them together: 2a+5a = 7a


Simplify 4a plus 7b plus 6a-3b-2a?

11a+7b-(3b-2a)


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


Simplify 7a plus 2a plus 1?

9a + 1


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


Simplify 3a plus 5 plus 2a plus 6?

5a + 11


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


What should be subtracted from a2 -4a2 plus 5a2-6 to obatain a2-2a plus 1?

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7


Simplify 9a plus 8 minus 2a minus 3 minus 5a?

2a+5


Simplify 2a plus 3a plus 4 equals?

2a + 3a + 4 = 5a + 4


Simplify 2a plus 3b plus 5a plus 6 plus 3b?

6+7a+6b


Simplify 2a plus 11a minus 5a?

2a + 11a - 5a = 8a


Simplify 5aยณ - 4ab plus 2aยณ as much as possible?

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.


What is -4 plus 10 plus 6a -2a plus 3?

-4 + 10 + 6a - 2a + 3 9 + 4a


Simplify the expression 3a plus 2b - c - 2a plus 5b plus 3c by combining like terms?

a + 7b + 2c


Simplify 3a4-2a2 plus 5a-10 - 2a4 plus 4a2 plus 5a-2 equals?

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)


Combine like terms and simplify 2b plus 2 minus 2a plus a squared 3?

There are no like terms here.


A plus a plus a-2a equals?

a + a + a - 2a = 3a - 2a = a


What is the answer to 6a plus 2 equals 2a plus 10?

A=2


Can someone Simplify the expression 3a plus 2b - c - 2a plus 5b plus 3c by combining like terms?

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.